2020
DOI: 10.3390/microorganisms8101560
|View full text |Cite
|
Sign up to set email alerts
|

The Neutrophil-to-Monocyte Ratio and Lymphocyte-to-Neutrophil Ratio at Admission Predict In-Hospital Mortality in Mexican Patients with Severe SARS-CoV-2 Infection (Covid-19)

Abstract: There is a deep need for mortality predictors that allow clinicians to quickly triage patients with severe coronavirus disease 2019 (Covid-19) into intensive care units at the time of hospital admission. Thus, we examined the efficacy of the lymphocyte-to-neutrophil ratio (LNR) and neutrophil-to-monocyte ratio (NMR) as predictors of in-hospital death at admission in patients with severe Covid-19. A total of 54 Mexican adult patients with Covid-19 that met hospitalization criteria were retrospectively enrolled,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
69
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 44 publications
5
69
1
3
Order By: Relevance
“…Of note, in that study, the impact of these markers on in-hospital mortality was not assessed and comparisons were made between SARS-CoV-2 positive and negative patients [ 42 ]. In a cohort of 54 Mexican adult patients with COVID-19, an LNR lower than 0.088 and an NMR greater than 17.75 measured at the time of hospital admission were independent risk factors for in-hospital mortality in patients with severe COVID-19 [ 43 ]. As mentioned early, several studies have reported impaired clinical outcomes, including more intensive care unit (ICU) admissions and increased mortality among CKD patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, in that study, the impact of these markers on in-hospital mortality was not assessed and comparisons were made between SARS-CoV-2 positive and negative patients [ 42 ]. In a cohort of 54 Mexican adult patients with COVID-19, an LNR lower than 0.088 and an NMR greater than 17.75 measured at the time of hospital admission were independent risk factors for in-hospital mortality in patients with severe COVID-19 [ 43 ]. As mentioned early, several studies have reported impaired clinical outcomes, including more intensive care unit (ICU) admissions and increased mortality among CKD patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…However, only the neutrophil-to-monocyte ratio remained a significant independent predictor of the primary outcome in the multivariate competing risk regression model. It has been observed that lymphocyte and monocyte populations decrease while neutrophil counts increase in COVID-19 ( Zhao et al, 2020 ), and more recent research showed a link between neutrophil-to-monocyte ratio and COVID-19 in-hospital mortality ( Rizo-Téllez et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The 15 most frequent tests corresponding to 38 biomarkers were selected for analysis based on the availability of data. Five biomarkers WBC count, neutrophil lymphocyte ratio (NLR), lymphocyte monocyte ration (LMR), neutrophil monocyte ratio (NMR), platelet to lymphocyte ratio (PLR) were manually calculated from various blood cell counts available owing their reported importance in predicting mortality due to COVID [21, 22]. 209 unique co-morbid conditions were observed in patients in our study.…”
Section: Methodsmentioning
confidence: 99%